Direct EFL Instruction for Gifted Students: A Case Study - Hidayati Utami; Ashadi Ashadi (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
This study aimed to describe the use of direct instruction in English learning for gifted students. This research applied a case study approach. The participants of this study were an English teacher and five students of a special junior high school for gifted students of grades 7 and 8 in the acceleration program. The data were collected through in-depth interview, focused-group interview, observation, and document analysis. The data were qualitatively analyzed through transcribing, data condensing, data displaying through a matrix, and conclusion drawing. The result showed that the teacher used the teaching strategies for direct instruction which were supported by some appropriate teaching aids. The impact of the strategies on the students were the students were actively involved in the teaching-learning process although they still encountered some difficulties in their English learning process. However, the teacher needed to employ other strategies which could meet the other needs of the gifted students in the teaching-learning process.